Mobile-Based Service Management Online Reservation Portal (Msmorp) Towards Continuous Quality Improvement - Mamaril , Julius Cesar (Southeast Asian Journal of Science and Technology, 2017)
This paper sought to identify the current profile of Joy and Jim Catering Services towards catering reservation and services in order to enumerate the functional and non-functional requirements of the business which will serve as basis in designing the components and features of a Mobile-based Service Management Online Reservation Portal (MSMORP) and evaluate whether the use of the online reservation system, indeed, has become essential in gearing towards the business goal of continuous quality improvement. The study utilized the descriptive method of research and the developmental type of research along with RAD (Rapid Application Development) as SDLC (System Development Life Cycle) method and the IPO (Input-Process-Output) software development framework. This methods and framework were used to describe the existing processes of the subject business, define the system features, and develop the system, respectively. Findings showed that a lot of catering services and reservation problems are encountered by the subject business and the integration of the developed system has helped it to mitigate such problems and provide service quality and the continuous use and implementation of MSMORP has helped the catering business significantly in attaining continuous quality improvement.